The influence of quaternary ammonium salts on mechanical properties of light-cured resin dental composites - Maja Zalega; Joanna Nowak; Kinga Bociong (Polimery)
The composite consisting of bis-GMA/UDMA/HEMA/TEGDMA monomer mixture forming apolymer matrix filled with silanized silica (45 wt%) was modified with CTAB or DODAB quaternary ammonium salts (0.5‒2.0 wt%). The hardness, flexural strength as well as diametrical tensile strength of the composite before and after modification were evaluated. The type and amount of salt affected the hardness, flexural strength, and shrinkage stress; however, they did not influence the diametral tensile strength of the tested composites.